Gamma , Γ, everywhere!

Calculus Level pending

0 e x 7 sin ( x 7 ) d x = sin ( π a ) Γ ( b c ) 2 q \large \int_0^∞ e^{-x^7} \sin(x^7)\ dx = \frac{\sin \left(\frac{\pi}{a}\right) \Gamma \left(\frac{b}{c} \right)}{\sqrt[q]{2}}

The equation above holds true for positive integers a a , b b , c c , and q q , with b b and c c being coprime integers.

Find the value of a ( b c ) q \dfrac {a(b-c)}q .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

I = 0 e x 7 sin x 7 d x By Euler’s formula: e θ i = cos θ + i sin θ = ( 0 e x 7 + x 7 i d x ) ( ) denotes the imaginary part function. = ( 0 t 6 7 e t 7 1 i 7 d t ) Let t = ( 1 i ) x 7 d t = 7 ( 1 i ) x 6 d x = ( Γ ( 1 7 ) 7 ( 1 i ) 7 ) Gamma function Γ ( s ) = 0 t s 1 e t d t = ( Γ ( 8 7 ) 2 e ( 2 n 1 4 ) π i 7 ) and Γ ( 1 + s ) = s Γ ( s ) = ( e 8 n + 1 28 π i Γ ( 8 7 ) 2 14 ) By Euler’s formula = ( ( cos ( 8 n + 1 ) π 28 + i sin ( 8 n + 1 ) π 28 ) Γ ( 8 7 ) 2 14 ) = sin ( 8 n + 1 ) π 28 Γ ( 8 7 ) 2 14 Checking with the numerical value of I = sin π 28 Γ ( 8 7 ) 2 14 \begin{aligned} I & = \int_0^\infty e^{-x^7} \blue{\sin x^7}\ dx & \small \blue{\text{By Euler's formula: }e^{\theta i} = \cos \theta + i\sin \theta} \\ & = \blue \Im \left(\int_0^\infty e^{-x^7 + \blue {x^7i}} \ dx \right) & \small \blue{\Im(\cdot) \text{ denotes the imaginary part function.}} \\ & = \Im \left(\int_0^\infty \frac {t^{-\frac 67}e^{-t}}{7\sqrt[7]{1-i}} dt \right) & \small \blue{\text{Let }t = (1-i)x^7 \implies dt = 7(1-i)x^6\ dx} \\ & = \Im \left(\frac \blue{\Gamma \left(\frac 17 \right)}{\blue 7 \red{\sqrt[7]{(1-i)}}} \right) & \small \blue{\text{Gamma function }\Gamma (s) = \int_0^\infty t^{s-1}e^{-t} dt} \\ & = \Im \left(\frac \blue{\Gamma \left(\frac 87 \right)}\red{\sqrt[7]{\sqrt 2 e^{\left(2n-\frac 14\right)\pi i}}} \right) & \small \blue{\text{and }\Gamma (1+s) = s \Gamma(s)} \\ & = \Im \left(\frac {e^{\frac {8n+1}{28} \pi i}\Gamma \left(\frac 87\right)}{\sqrt[14]2} \right) & \small \red{\text{By Euler's formula}} \\ & = \Im \left(\frac {\left(\cos \frac {(8n+1)\pi}{28} + i\sin \frac {(8n+1)\pi}{28} \right) \Gamma \left(\frac 87\right)}{\sqrt[14]2} \right) \\ & = \frac {\blue{\sin \frac {(8n+1)\pi}{28}}\Gamma \left(\frac 87\right)}{\sqrt[14]2} & \small \blue{\text{Checking with the numerical value of }I} \\ & = \frac {\blue{\sin \frac \pi {28}} \Gamma \left(\frac 87\right)}{\sqrt[14]2} \end{aligned}

Therefore a ( b c ) q = 28 ( 8 7 ) 14 = 2 \dfrac {a(b-c)}q = \dfrac {28(8-7)}{14} = \boxed 2 .

1 i 1 - i is not necessarily equal to 2 e π / 4 i \sqrt2 e^{-\pi/4 \, i } . It could also be equal to 2 e ( π / 4 + 100000 π ) i \sqrt2 e^{(-\pi/4 + 100000\pi)i } .

Your solution is incomplete.

Pi Han Goh - 6 months, 1 week ago

Log in to reply

Okay teacher.

Chew-Seong Cheong - 6 months, 1 week ago

0 e x 7 sin ( x 7 ) d x = 1 2 i ( 0 e x 7 + i x 7 0 e x 7 i x 7 d x ) \int_0^∞ e^{-x^7} \sin(x^7)dx = \frac{1}{2i}(\int_0^∞ e^{-x^7 +ix^7} - \int_0^∞ e^{-x^7-ix^7}dx) As s i n x = e i x e i x 2 i sinx= \frac{e^{ix}-e^{-ix}}{2i}

Take x 7 = u x^7 = u then the integral becomes 1 14 i ( 0 u 6 / 7 e u ( 1 i ) d u 0 u 6 / 7 e u ( 1 + i ) d u ) \frac{1}{14i}(\int_0^∞ u^{-6/7}e^{-u(1-i)} du-\int_0^∞ u^{-6/7} e^{-u(1+i)} du) Take u ( 1 i ) = t , a n d , u ( 1 + i ) = p u(1-i) = t , and , u(1+i) = p Then the integral becomes 1 14 i ( 1 i ) 1 / 7 0 t 6 / 7 e t d t 1 14 i ( 1 + i ) 1 / 7 0 p 6 / 7 e p d p \frac{1}{14i(1-i)^{1/7}} \int_0^∞ t^{-6/7} e^{-t}dt -\frac{1}{14i(1+i)^{1/7}} \int_0^∞ p^{-6/7} e^{-p}dp Which is Γ ( 1 7 ) ( 1 14 i ( 1 i ) 1 / 7 1 14 i ( 1 + i ) 1 / 7 ) Γ(\frac{1}{7} ) (\frac{1}{14i(1-i)^{1/7}} - \frac{1}{14i(1+i)^{1/7}} ) ( 1 i ) 1 / 7 = 2 14 e π i / 28 , ( 1 + i ) 1 / 7 = 2 14 e π i / 28 (1-i)^{1/7} = \sqrt[14]{2} e^{-πi/28} , (1+i)^{1/7} = \sqrt[14]{2} e^{πi/28} So the integral will be 1 14 i ( 2 14 ) Γ ( 1 / 7 ) ( 2 i sin ( π 28 ) ) \frac{1}{14i(\sqrt[14]{2})}Γ(1/7)(2i \sin(\frac{π}{28}))

Answer is Γ ( 8 7 ) sin ( π 28 ) 2 14 \boxed{\frac{Γ(\frac{8}{7}) \sin(\frac{π}{28})}{\sqrt[14]{2}}}

@Dwaipayan Shikari , you should put a backslash "\" in front of all functions such as \sin x ( sin x \sin x ). Note that sin is not in italic but x is in italic and there is a space between sin and x. Note i sin x ( i s i n x ) i sin x) , there are spaces among them but i \sin x ( i sin x i \sin x ) is with the spaces.

You can enter \pi π \pi , \Gamma Γ \Gamma , \alpha α \alpha , \beta β \beta , etc. You can also enter \frac bc b c \frac bc and \dfrac \pi 2 π 2 \dfrac \pi 2 .

You have to mention b b and c c be coprime integers. Because 8 7 = 16 14 = 24 21 \frac 87 = \frac {16}{14} = \frac {24}{21} \cdots , there are infinitely many solutions.

I have amended the problem statement for you.

Chew-Seong Cheong - 6 months, 1 week ago

Log in to reply

Thanking you 😃

Dwaipayan Shikari - 6 months, 1 week ago
Karan Chatrath
Dec 3, 2020

I = 0 e x 7 sin x 7 d x I = \int_{0}^{\infty} \mathrm{e}^{-x^7} \sin{x^7} \ dx

Let: x 7 = z x^7=z . This transforms the integral to:

I = 1 7 0 e z sin z z 6 / 7 d z I = \frac{1}{7}\int_{0}^{\infty} \mathrm{e}^{-z} \sin{z} \ z^{-6/7} \ dz

Knowing that:

sin z = e i z e i z 2 i \sin{z} = \frac{\mathrm{e}^{iz} - \mathrm{e}^{-iz}}{2i}

I = 1 7 0 e z ( e i z e i z 2 i ) z 6 / 7 d z \implies I =\frac{1}{7}\int_{0}^{\infty} \mathrm{e}^{-z} \left( \frac{\mathrm{e}^{iz} - \mathrm{e}^{-iz}}{2i}\right) \ z^{-6/7} \ dz I = 1 14 i ( 0 e ( 1 i ) z z 6 / 7 d z 0 e ( 1 + i ) z z 6 / 7 d z ) \implies I = \frac{1}{14i}\left(\int_{0}^{\infty} \mathrm{e}^{-(1-i)z} \ z^{-6/7} \ dz - \int_{0}^{\infty} \mathrm{e}^{-(1+i)z} \ z^{-6/7} \ dz\right)

Let:

J ( a ) = 0 e a z z 6 / 7 d z J (a)= \int_{0}^{\infty} \mathrm{e}^{-az} \ z^{-6/7} \ dz I = 1 14 i ( J ( 1 i ) J ( 1 + i ) ) \implies I =\frac{1}{14i}\left(J(1-i) -J(1+i)\right)

Taking a z = t az = t transforms the integral to:

J ( a ) = 1 a 1 / 7 0 e t t 6 / 7 d t J(a) = \frac{1}{a^{1/7}}\int_{0}^{\infty} \mathrm{e}^{-t} \ t^{-6/7} \ dt J ( a ) = Γ ( 1 7 ) a 1 / 7 J(a) = \frac{\Gamma\left(\frac{1}{7}\right)}{a^{1/7}}

The above is obtained using the definition of the Gamma function. Plugging the above result in I I gives:

I = 1 14 i ( J ( 1 i ) J ( 1 + i ) ) I = \frac{1}{14i}\left(J(1-i) -J(1+i)\right) I = Γ ( 1 7 ) 7 ( 2 i ) ( 1 ( 1 i ) 1 / 7 1 ( 1 + i ) 1 / 7 ) I = \frac{\Gamma\left(\frac{1}{7}\right)}{7(2i)}\left( \frac{1}{(1-i)^{1/7} }- \frac{1}{(1+i)^{1/7}}\right) I = Γ ( 8 7 ) 2 i ( 1 ( 1 i ) 1 / 7 1 ( 1 + i ) 1 / 7 ) I = \frac{\Gamma\left(\frac{8}{7}\right)}{2i}\left( \frac{1}{(1-i)^{1/7} }- \frac{1}{(1+i)^{1/7}}\right) Γ ( n + 1 ) = n Γ ( n ) \because \Gamma(n+1) = n \Gamma(n)

Now: 1 i = 2 e i π / 4 1-i = \sqrt{2} \mathrm{e}^{-i\pi/4} ( 1 i ) 1 / 7 = 2 1 / 14 e i π / 28 (1-i)^{1/7} = 2^{1/14} \mathrm{e}^{-i\pi/28}

Similarly:

( 1 + i ) 1 / 7 = 2 1 / 14 e i π / 28 (1+i)^{1/7} = 2^{1/14} \mathrm{e}^{i\pi/28}

Plugging these results and simplifying:

I = Γ ( 8 7 ) 2 i ( e i π / 28 e i π / 28 ) 1 2 1 / 14 I = \frac{\Gamma\left(\frac{8}{7}\right)}{2i}\left(\mathrm{e}^{i\pi/28} - \mathrm{e}^{-i\pi/28}\right)\frac{1}{2^{1/14}} I = Γ ( 8 7 ) sin ( π 28 ) 2 1 / 14 \implies I = \frac{\Gamma\left(\frac{8}{7}\right)\sin\left(\frac{\pi}{28}\right)}{2^{1/14}}

Thanking you for interacting sir!

Dwaipayan Shikari - 6 months, 1 week ago

Log in to reply

Welcome and thanks for posting this problem.

Karan Chatrath - 6 months, 1 week ago

Consider the integral, with n > 0 n > 0 ,

I n = 0 e x n sin x n d x . \begin{aligned} I_n = \int_{0}^{\infty} e^{-x^{n}} \sin{x^{n}} \, dx . \end{aligned}

Substitute with t = x n t = x^n , we have

I n = 1 n 0 t 1 n 1 e t sin t d t \begin{aligned} I_n = \frac{1}{n} \int_{0}^{\infty} t^{\frac{1}{n} - 1} e^{-t} \sin{t} \, dt \end{aligned}

Define

J n 1 ( z ) = 0 t 1 n 1 e t sin z t d t \begin{aligned} J_n^1(z) = \int_{0}^{\infty} t^{\frac{1}{n} - 1} e^{-t} \sin{zt} \, dt \end{aligned}

and

J n 2 ( z ) = 0 t 1 n 1 e t cos z t d t . \begin{aligned} J_n^2(z) = \int_{0}^{\infty} t^{\frac{1}{n} - 1} e^{-t} \cos{zt} \, dt . \end{aligned}

It follows that

d d z J n 1 ( z ) = 0 t 1 n e t cos z t d t = [ t 1 n e t 1 + z 2 ( cos z t + z sin z t ) ] 0 1 n ( 1 + z 2 ) 0 t 1 n 1 e t ( cos z t + z sin z t ) d t , (Integrate by part with u = t 1 / n , d v = e t cos z t d t ) = z n ( 1 + z 2 ) J n 1 + 1 n ( 1 + z 2 ) J n 2 \begin{aligned} \frac{d}{dz} J_n^1(z) & = \int_{0}^{\infty} t^{\frac{1}{n}} e^{-t} \cos{zt} \, dt \\ & = \left[ \frac{t^{\frac{1}{n}} e^{-t}}{1 + z^2} (-\cos{zt} + z\sin{zt}) \right]_{0}^{\infty} - \frac{1}{n(1+z^2)} \int_0^{\infty} t^{\frac{1}{n}-1} e^{-t} (-\cos{zt} + z \sin{zt}) \, dt \, \text{ , (Integrate by part with} \, u = t^{1/n}, dv = e^{-t} \cos{zt} dt \text{)} \\ & = - \frac{z}{n(1+z^2)}J_n^1 + \frac{1}{n(1+z^2)}J_n^2 \end{aligned}

and

d d z J n 2 ( z ) = 0 t 1 n e t sin z t d t = [ t 1 n e t 1 + z 2 ( sin z t z cos z t ) ] 0 + 1 n ( 1 + z 2 ) 0 t 1 n 1 e t ( sin z t + z cos z t ) d t , (Integrate by part with u = t 1 / n , d v = e t sin z t d t ) = 1 n ( 1 + z 2 ) J n 1 z n ( 1 + z 2 ) J n 2 . \begin{aligned} \frac{d}{dz} J_n^2(z) & = -\int_{0}^{\infty} t^{\frac{1}{n}} e^{-t} \sin{zt} \, dt \\ & = \left[ -\frac{t^{\frac{1}{n}} e^{-t}}{1 + z^2} (-\sin{zt} - z\cos{zt}) \right]_{0}^{\infty} + \frac{1}{n(1+z^2)} \int_0^{\infty} t^{\frac{1}{n}-1} e^{-t} (-\sin{zt} + z \cos{zt}) \, dt \, \text{ , (Integrate by part with} \, u = t^{1/n}, dv = e^{-t} \sin{zt} dt \text{)} \\ & = - \frac{1}{n(1+z^2)}J_n^1 - \frac{z}{n(1+z^2)}J_n^2 . \end{aligned}

We can write this system of differential equations as

d d t [ J n 1 ( z ) J n 2 ( z ) ] = [ z n ( 1 + z 2 ) 1 n ( 1 + z 2 ) 1 n ( 1 + z 2 ) z n ( 1 + z 2 ) ] [ J n 1 ( z ) J n 2 ( z ) ] \begin{aligned} \frac{d}{dt} \begin{bmatrix} J_n^1(z) \\ J_n^2(z) \end{bmatrix} = \begin{bmatrix} -\frac{z}{n(1+z^2)} & \frac{1}{n(1+z^2)} \\ -\frac{1}{n(1+z^2)} & -\frac{z}{n(1+z^2)} \end{bmatrix} \begin{bmatrix} J_n^1(z) \\ J_n^2(z) \end{bmatrix} \end{aligned}

with initial condition

[ J n 1 ( 0 ) J n 2 ( 0 ) ] = [ 0 t 1 n 1 e t sin 0 t d t 0 t 1 n 1 e t cos 0 t d t ] = [ 0 Γ ( 1 n ) ] \begin{aligned} \begin{bmatrix} J_n^1(0) \\ J_n^2(0) \end{bmatrix} = \begin{bmatrix} \int_{0}^{\infty} t^{\frac{1}{n} - 1} e^{-t} \sin{0t} \, dt \\ \int_{0}^{\infty} t^{\frac{1}{n} - 1} e^{-t} \cos{0t} \, dt \end{bmatrix} = \begin{bmatrix} 0 \\ \Gamma(\frac{1}{n}) \end{bmatrix} \end{aligned}

Let

A ( z ) = [ z n ( 1 + z 2 ) 1 n ( 1 + z 2 ) 1 n ( 1 + z 2 ) z n ( 1 + z 2 ) ] . \begin{aligned} A(z) = \begin{bmatrix} -\frac{z}{n(1+z^2)} & \frac{1}{n(1+z^2)} \\ -\frac{1}{n(1+z^2)} & -\frac{z}{n(1+z^2)} \end{bmatrix} . \end{aligned}

Then,

0 z A ( z ) d z = [ 1 2 n log ( 1 + z 2 ) 1 n arctan z 1 n arctan z 1 2 n log ( 1 + z 2 ) ] \begin{aligned} \int_{0}^{z} A(z) \, dz = \begin{bmatrix} -\frac{1}{2n} \log{(1+z^2)} & \frac{1}{n} \arctan{z} \\ -\frac{1}{n} \arctan{z} & -\frac{1}{2n} \log{(1+z^2)} \end{bmatrix} \end{aligned}

and

e 0 z A ( z ) d z = [ ( 1 + z 2 ) 1 2 n cos ( arctan z n ) ( 1 + z 2 ) 1 2 n sin ( arctan z n ) ( 1 + z 2 ) 1 2 n sin ( arctan z n ) ( 1 + z 2 ) 1 2 n cos ( arctan z n ) ] . \begin{aligned} e^{\int_{0}^{z} A(z) \, dz} = \begin{bmatrix} (1+z^2)^{-\frac{1}{2n}} \cos{(\frac{\arctan{z}}{n})} & (1+z^2)^{-\frac{1}{2n}} \sin{(\frac{\arctan{z}}{n})} \\ -(1+z^2)^{-\frac{1}{2n}} \sin{(\frac{\arctan{z}}{n})} & (1+z^2)^{-\frac{1}{2n}} \cos{(\frac{\arctan{z}}{n})} \end{bmatrix} . \end{aligned}

The solution of the differential equations is

[ J n 1 ( z ) J n 2 ( z ) ] = e 0 z A ( z ) d z [ J n 1 ( 0 ) J n 2 ( 0 ) ] = [ ( 1 + z 2 ) 1 2 n cos ( arctan z n ) ( 1 + z 2 ) 1 2 n sin ( arctan z n ) ( 1 + z 2 ) 1 2 n sin ( arctan z n ) ( 1 + z 2 ) 1 2 n cos ( arctan z n ) ] [ 0 Γ ( 1 n ) ] = [ ( 1 + z 2 ) 1 2 n sin ( arctan z n ) Γ ( 1 n ) ( 1 + z 2 ) 1 2 n cos ( arctan z n ) Γ ( 1 n ) ] \begin{aligned} \begin{bmatrix} J_n^1(z) \\ J_n^2(z) \end{bmatrix} = e^{\int_{0}^{z} A(z) \, dz} \begin{bmatrix} J_n^1(0) \\ J_n^2(0) \end{bmatrix} = \begin{bmatrix} (1+z^2)^{-\frac{1}{2n}} \cos{(\frac{\arctan{z}}{n})} & (1+z^2)^{-\frac{1}{2n}} \sin{(\frac{\arctan{z}}{n})} \\ -(1+z^2)^{-\frac{1}{2n}} \sin{(\frac{\arctan{z}}{n})} & (1+z^2)^{-\frac{1}{2n}} \cos{(\frac{\arctan{z}}{n})} \end{bmatrix} \begin{bmatrix} 0 \\ \Gamma(\frac{1}{n}) \end{bmatrix} = \begin{bmatrix} (1+z^2)^{-\frac{1}{2n}} \sin{(\frac{\arctan{z}}{n})} \Gamma(\frac{1}{n}) \\ (1+z^2)^{-\frac{1}{2n}} \cos{(\frac{\arctan{z}}{n})} \Gamma(\frac{1}{n}) \end{bmatrix} \end{aligned}

Finally, the given integral, using n = 7 n = 7 , can be evaluated as

I 7 = 1 7 J 7 1 ( 1 ) = sin ( π 28 ) Γ ( 8 7 ) 2 14 \begin{aligned} I_7 & = \frac{1}{7} J_7^1(1) \\ & = \frac{\sin{(\frac{\pi}{28})} \Gamma(\frac{8}{7})}{\sqrt[14]{2}} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...